Comparative biological characteristics of pea (Pisum sativum) varieties - KOSEV, VALENTIN; VASILEVA, VILIANA (The Indian Journal of Agricultural Sciences, 2021)
Some basic quantitative signs and phenological indicators were analyzed for samples of seven forage peas (Pisum sativum L.) of different origins. Plant material from both, aboveground and root biomass was analyzed: i) in the beginning of flowering stage: plant height (cm), fresh stem weight (g), dry stem weight (g), root length (cm), fresh root mass weight (g), dry root mass weight (g), nodules per plant and nodule weight per plant (g); in the technological maturity of seeds stage: number of pods per plant, number of seeds per plant, seed weight per plant (g), number of seeds per pod and seed weight per pod (g). Broad sense heritability (Hbs) was calculated. Hierarchical cluster analysis was applied for the grouping of genotypes by similarity and correlation analysis for the finding the relationships between the signs and their variability. Specimens which meet the highest plant length requirements, green mass yield root length, number and weight of nodules were shown. They are considered as suitable for inclusion as parent components in future breeding programs. Some correlations were found, i.e. between the fresh stem weight and the nodules (r = +0.951), between the nodule number and the root length (r = +0.949) and between the weight and the number of seeds (r = +0.950). The findings could be of use for the breeding process in peas.